Pólos tecnológicos e indústria de alta tecnologia: o caso de São Carlos-SP - Marighetti, Alex [UNESP] (2013)
The present work aims to identify and analyze the technological pole and the high technology industries in the process of territorial development in the municipality of São Carlos, SP, in the interior of the State of São Paulo. San Carlos is, today, one of the main industrial centers and technology of the State of São Paulo. The municipality has the title capital of technology due to the large public investment and/or private ensuring its prominent position in the sector of information technology, electronics etc. easy access to the city by motorway, the high rates of technological development of the region and the deconcentration of industrial state, characterized by the processes of globalization and migration, confer to the industrial sector especially in the city, in its administrative region and, consequently, in the State of São Paulo. Therefore, the objective of this work is: to analyze the changes resulting from the transition from fordism to flexible accumulation; indicate the studies about the technological poles and definition of the industry sectors characterized as high-technology in Brazil and in the world; to analyze the new territorialities produced in the municipality from the consolidation of the technological pole; emphasizing the role of structural elements of technological pole (high-technology industry, universities and research centers) in the municipality; raise possible contradictions inherent to the process of economic development trailer the installation of these technological poles. It is hoped, to contribute, through the dissemination of the results, promote the advancement of geographic knowledge